Nonverbal Communication of Employees with Disabilities (Phenomenological Study of Employees with Disabilities at Isyarat Steam Motor Bandar Lampung) - Weni Safitri; M Denu Poyo; Budhi Waskito (Penerbit Jurnal Indonesia, 2025)
This study explores the use of nonverbal communication among employees with hearing disabilities at Isyarat Steam Motor Bandar Lampung. The study aims to understand how deaf employees interact with customers and managers using alternative communication strategies. As the importance of inclusion in the workplace increases, this study provides insights into how communication can be maintained effectively despite physical limitations. A qualitative method with a phenomenological approach was used to collect data through observation, in-depth interviews, and document analysis. Participants included deaf employees, customers, and business managers. The results showed that employees communicated nonverbally using BISINDO (Indonesian Sign Language), written messages, facial expressions, gestures, and mobile applications. These tools helped bridge communication gaps and supported smooth interactions in daily operations. Customers responded positively to these interactions, often expressing interest and appreciation for employees' ability to provide professional service. These findings confirm that nonverbal communication not only facilitates interactions in the workplace but also strengthens employees' sense of belonging and self-confidence. In conclusion, nonverbal communication plays a vital role in building an inclusive and respectful work environment, as well as promoting social and economic empowerment for people with disabilities